Spatial Spillover Effects Promote the Overall Improvement of Urban Competitiveness: Evidence of SDM in Asian Cities - Cheyuan Liu; Cheyuan Liu; Michael Yao-Ping Peng; Weijin Gong (Frontiers in Environmental Science, 2022)
The competitiveness of a city is in the process of competitive development. This study uses the Spatial Dubin Model (SDM) technique to explore the influencing factors and spatial spillover effects of the economic competitiveness of 565 cities in Asia. The study finds that the factor spillover bandwidth affecting the improvement of urban competitiveness is primarily concentrated in the range of 1,000 km. Furthermore, with a maximum elasticity value of roughly 11.6%, a city’s spatial spillover effect is a crucial factor in selecting strategies for enhancing its competitiveness level. Financial services, industrial structure, and human resources all have an influence on the level of urban competitiveness. Therefore, in order to better improve the level of regional urban competitiveness, one is to improve the overall level of factors affecting urban competitiveness and enhance the competitiveness of the city itself; the other is to enhance the flow of factors between regions and make full use of the space of factors Spillover effects enhance the level of regional competitiveness; the third is to enhance the spatial interaction between regions and use the externality of urban competitiveness to achieve an overall improvement in the level of regional competitiveness.